Subthreshold Vibrotactile Noise Stimulation Immediately Improves Manual Dexterity in a Child With Developmental Coordination Disorder: A Single-Case Study - Nobusako, Satoshi; Osumi, Michihiro; Matsuo, Atsushi; Furukawa, Emi; Maeda, Takaki; Shimada, Sotaro; Nakai, Akio; Morioka, Shu (Frontiers in Neurology, 2019)
Developmental coordination disorder (DCD) is the most common childhood movement disorder. It is characterized by clumsiness of fine and gross motor skills in developing children. Children with DCD have low ability to effectively use tactile information for movements, instead relying on visual information. In addition, children with DCD have deficits in visuo-motor temporal integration, which is important in motor control. These traits subsequently lead to clumsiness of movements. Conversely, however, imperceptible vibrotactile noise stimulation (at 60%-intensity of the sensory threshold) to the wrist provides stochastic resonance (SR) phenomenon to the body, improving the sensory and motor systems. However, the effects of SR have not yet been validated in children with DCD. Thus, we conducted a single case study of a 10-year-old boy with a diagnosis of DCD to investigate the effect of SR on visual dependence, visuo-motor temporal integration, and manual dexterity. SR was provided by vibrotactile noise stimulation (at an intensity of 60% of the sensory threshold) to the wrist. Changes in manual dexterity (during the SR on- and off-conditions) were measured using the manual dexterity test of the Movement Assessment Battery for Children-2nd edition. The point of subjective equality measured by visual or tactile temporal order judgment task served as a quantitative indicator reflecting specific sensory dependence. The delay detection threshold and steepness of delay detection probability curve, which were measured using the delayed visual feedback detection task, were used as quantitative indicators of visuo-motor temporal integration. The results demonstrated alleviated visual dependence and improved visuo-motor temporal integration during the SR on-conditions rather than the SR off-conditions. Most importantly, manual dexterity during the SR on-conditions was significantly improved compared to that during the SR off-conditions. Thus, the present results highlighted that SR could contribute to improving poor movement in children with DCD. However, since this was a single case study, a future interventional study with a large sample size is needed to determine the effectiveness of SR for children with DCD.